A Joint Representation of Rényi’s and Tsalli’s Entropy with Application in Coding Theory - Litegebe Wondie; Satish Kumar (International Journal of Mathematics and Mathematical Sciences)
We introduce a quantity which is called Rényi’s-Tsalli’s entropy of order ξ and discussed some of its major properties with Shannon and other entropies in the literature. Further, we give its application in coding theory and a coding theorem analogous to the ordinary coding theorem for a noiseless channel is proved. The theorem states that the proposed entropy is the lower bound of mean code word length.